Zmiany w wydatkach inwestycyjnych w zakładach przetwórstwa żywca wieprzowego na Podkarpaciu w latach 1999-2004 - Stec, Artur (Changes in Investment Expenditures in Pork Processing Plants in Podkarpackie Province in the Years 1999-2004, 2006)
Processes aiming at adapting meat processing sector in Poland, were a great investment effort for meat plants. The means were taken from own funds of the plants, bank loans, preferential credits and pre-accession funds. Microenterprises and small companies financed the restructuring process first of all from their own funds. Managements of meat plants, which did not try to get preferential credits and pre-accession funds, acted like that due to having doubts about its effectiveness and time- consuming procedures preceding receiving the money needed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 607-613